Myriad of Traumatic Oral Soft Tissue Pathologies: A 12-Year Histopathological Experience - Madhur Sharma; Anjali Narwal; Gopikrishnan Vijayakumar; Mala Kamboj; Anju Devi (Online Journal of Health & Allied Sciences)
Objective: To identify the prevalence of oral soft tissue pathologies associated with trauma and further propose a working classification of the same based on histopathological experience. Material and Methods: An observational retrospective study was conducted on all trauma associated soft tissue lesions of oral cavity in a tertiary care hospital (2010-2022). The collected data was tabulated and analyzed. An attempt was also made to fabricate a working classification based on frequency of occurrence of these traumatic soft tissue pathologies. Results: Soft tissue oral pathologies associated with trauma ranged from benign lesions like mucocele and traumatic fibroma to malignancies like oral squamous cell carcinoma. Significant differences in age, gender and site predilection of these entities were obtained. Conclusion: This category of lesions has been frequently overlooked and not many studies have focused this aspect. An overview about the demographics of such commonly encountered trauma associated pathologies is essential for a dental practitioner to achieve better treatment and classification of these lesions based on their frequency is equally essential for better practice.